Perceptions of Music and its Effect on the Productivity of Students - Kahar, Nailah; Abalos, Cris Angel; Manero, Hannah Nicole; Mosquera, Duchess Siena Ross; Gonzales, Lenygel Benace; Asoy, Vivialyn; Estrellan, Joselyn; Marcell, April Mae (ASEAN Journal of Educational Research and Technology, 2024)
This study focused on the students’ perceptions of music and its effect on their productivity by using the double-phase, sequential mixed methods approach. The study also aimed to undermine the greatly preferred genre, its influence on prompt academic submissions, its impact on efficient study sessions, its aid in progressive academic tasks, its enhancement on scholastic concentration, the students’ perceptions, and whether there is a significant relationship between the preferred genre and the productivity. Out of the genres given which were country, instrumental, pop, rhythm and blues, and rock, the students highly preferred pop to increase their productivity. The ratings on the effects of listening to music on the student’s productivity in terms of prompt academic submissions and progressive academic tasks have their highest verbal description of “agree” implying that music greatly aids in the completion of academic tasks or requirements. Efficient study sessions and enhanced scholastic concentration received its highest verbal description of “neutral”, meaning medium contribution to not divert their focus while studying. There was no significant relationship found between the preferred genre and the increase in productivity. Overall, the usage of music in the academic productivity of students resonates with music as a way of motivation.